Urban Sprawl in Yogyakarta: An Analysis of Urban Morphology in Sinduadi Village in 2021 - Cahyani, Anggi; Giyarsih, Sri Rum (Jurnal Kawistara, 2024)
Urban sprawl has become a concern in development because of its negative impact onsustainable development. Such a special trend is apparent in the transformation of a peri-urban area of Sinduadi Village that is directly affected by the city of Yogyakarta. The village is most likely affected by the urban sprawl phenomenon in the city of Yogyakarta, especially on the morphological aspect of the urban morphology. This study aims to analyze the urban morphology in the Sinduadi Village in 2021 as a result of the urban sprawl of Yogyakarta City. Using quantitative methods, this research is based on a primary data of obtained from field surveys through probability sampling method. The research data came from image interpretation and attribute data processing using ArcGIS 10.3 Software. Secondary data was obtained through Sentinel 2A Imagery while primary data was The data analysis used in this research is quantitative descriptive analysis and spatial analysis using maps. The analysis of the morphological form of the city is carried out by analysis of overlapping maps. This research found that the morphology of the city in the Sinduadi Village in 2021 is linear based on the center of the area on Magelang street This marked by activities in the center of the area are dominated by commercial activities, namely, trade and service. Therefore, regional needs can be accommodated. The center of the area has a high building density (BCR>70%). High densityresidential land surrounds the center of the area and its development follows a grid and spinal road network pattern. These findings show that Sinduadi village has experienced urban sprawl marked by development trend that trespasses its under bounded city.